2008
DOI: 10.1007/s10705-008-9220-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of input level and crop diversity on soil nitrate-N, extractable P, aggregation, organic C and N, and nutrient balance in the Canadian Prairie

Abstract: A field experiment was conducted from 1995 to 2006 on a Dark Brown Chernozem (Typic Boroll) loam soil at Scott, Saskatchewan, Canada to determine the influence of input level and crop diversity on accumulation and distribution of nitrate-N and extractable P in the soil profile, and soil pH, dry aggregation, organic C and N, and nutrient balance sheets in the second 6-year rotation cycle (2001)(2002)(2003)(2004)(2005)(2006). Treatments were combinations of three input levels (organic input under conventional ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 63 publications
4
48
0
Order By: Relevance
“…They also have reduced potential for nitrate leaching (Malhi et al 2009) and tend to be more efficient in their energy use and produce lower levels of GHG emissions (Zentner et al 2011b). Including legumes in rotation may have a relatively large impact on GHG emissions and energy use due to biological nitrogen (N) fixation (BNF) and the accompanying reduction in N fertilizer requirements (Asgedom and Kebreab 2011).…”
Section: Crop Selection and Crop Rotationmentioning
confidence: 99%
See 2 more Smart Citations
“…They also have reduced potential for nitrate leaching (Malhi et al 2009) and tend to be more efficient in their energy use and produce lower levels of GHG emissions (Zentner et al 2011b). Including legumes in rotation may have a relatively large impact on GHG emissions and energy use due to biological nitrogen (N) fixation (BNF) and the accompanying reduction in N fertilizer requirements (Asgedom and Kebreab 2011).…”
Section: Crop Selection and Crop Rotationmentioning
confidence: 99%
“…Their deep root systems are able to retrieve nutrients from subsoil, thus reducing nitrate leaching, and can sequester C deep in the profile Olmstead and Brummer 2008;Malhi et al 2009). Perennial forages also provide habitat for wildlife, in particular nesting birds and pollinators (Jefferson et al 1999;Carvell et al 2006;Arnold et al 2007).…”
Section: Perennial Crops In Rotationmentioning
confidence: 99%
See 1 more Smart Citation
“…Amount of mineral nitrogen forms like ammonium and nitrate in soil depends on the amount of humus, C:N ratio, fertilizers and climatic conditions. So these forms of nitrogen content varied greatly between the years and within the year [19]. Application of fertilizers in summer increases the soil nitrate and ammonium content [20].…”
Section: Resultsmentioning
confidence: 99%
“…They also reported higher N uptake with alfalfa mulch treatments than with synthetic fertilizers in the wheat and second-year oat crop, and the oat crop also had a higher grain yield. Malhi et al [34] reported that organic cropping systems employing some form of fallow, or green manure partial-fallow, tend to accumulate more nitrate-N in the rooting zone than high input systems. They further suggested that fallow systems employing a green manure limited leaching because they temporarily stored available nitrate-N, while using soil water that could drive leaching, compared with fallow that excluded vegetation.…”
Section: Weed Managementmentioning
confidence: 99%